On the radio : effectiveness of the viva seguro financial education program (2014)
Through a randomized control trial this paper estimates the impact that a radio broadcasted financial education program has on the knowledge and behavior of its listeners. Viva Seguro, the program evaluated, is specialized on topics related with the risks individuals face and how to correctly address them including strategies related with savings and insurance. TTT and ITT estimations reveal that giving financial education through such mass media channel has a positive causal impact on the knowledge of risks individuals face and the number of insurance they know exist. No effect however is found on the knowledge of specific concepts of insurance, individual's attitudes towards them, their savings behavior nor the number of insurance they bought. These results are congruent with the program's structure and time devoted to each subject suggesting that, if correctly designed, mass media can be a cost effective mechanism through which the knowledge of individuals regarding insurance can be enhanced.